The mirthless world of the bilingual dictionary - Otto Hietsch (Linguistica, 1980)
A Critical Look at Two GermanEnglish Examples, and A Glossary. Officers, without a word of German, were billeted on fam ilies, and the town swarmed witb G.I.s. Lucia, whose English was always considered so good, had great difficulty in under standing what they said. She had a bewildered feeling of not being able - in the language sense - to 'hear' the phrases used. 'It beats the crap outa me,' she heard one say. She could not find the key-word in her English-German dictionary. Nor many other words they used. Ethel Mannin, Bavarian Story (London: Arrow Books, 1964), pp.143f. (abridged). Lucia's plight in 1945, and that of untold other non-native speakers before and after, is a common one.In the three decades and a half since then, some very good bilingual dictionaries in the pocket-size, desk and encyclopaedic ranges have been published. Yet, in spite of the praises that have been sung about such publications, most of them fail to do justice both to the richness of the spoken language on either side, and to the many ways , and means by which that richness can, and should, be matched level for level. Such a discovery is as inevi table as it is disconcerting.These general dictionaries, both in what they offer and in what they withhold, are, all in all, a sadly distorted reflection of living speech: far too frequently their renderings merely approximate to the usage of native speakers.